SEMIOTIC ANALYSIS BY CHARLES SANDERS PEIRCE ON THE LUMINTU BATIK MOTIF IN THE TRADITIONAL CLOTHING IN GAGRAK SEMARANG REGENCY - Ardaningrum, Viska Yuni; Syakir (Universitas Negeri Semarang, 2025)
Semarang Regency is located between the mountains and the coast, so it has a variety of potentials that become the strength of the region. Starting from the natural potential of plantations and agriculture to its culture. One of the unique cultural heritages in Semarang Regency is Lumintu Batik with its motifs depicting the potential of the region. The main motifs, namely the New Klinting Snake and Gedongsongo Temple, are also motifs from regional plantation products. Lumintu Batik is a work of art that reflects the identity of Semarang Regency. This research aims to identify and analyze the semiotic meaning of Lumintu Batik motifs in Semarang Regency Gagrak traditional clothing based on Charles Sanders Peirce's semiotic theory. This research is a descriptive qualitative research. The data in this study were obtained from direct observation at Batik Adisty Gallery, interviews with Batik Lumintu craftsmen, literature review, and documentation. The results of this research describe each form of Batik Lumintu motif and explain the semiotic analysis contained in the motif as an effort to preserve local potential and maintain batik as the original cultural heritage of Semarang Regency. Each batik motif is a sign and has a special meaning in it. This research contributes to readers in understanding the cultural values in batik motifs in the clothes they wear, reminding people of the importance of protecting the environment so that it remains sustainable and continues to develop, and being proud of regional culture.